1997
DOI: 10.1002/hep.510250113
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Variceal Ligation Is Superior to Combined Ligation and Sclerotherapy for Esophageal Varices: A Multicenter Prospective Randomized Trial

Abstract: rate could be lowered [3][4][5][6][7][8] and survival prolonged. 4,6,9,10 Studies Patients who have bled from varices remain at risk with rubber band ligation have shown that in addition to for rebleeding. There is interest in methods that would being safer than sclerotherapy, 11-14 ligation can further lower enable rapid eradication of varices. The present trial the rebleeding rate 12,13 and further improve survival. 11 Howwas designed to study whether combining ligation with ever, the problem of rebleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
3
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(53 citation statements)
references
References 19 publications
1
46
3
3
Order By: Relevance
“…Our study demonstrated an overall re-bleeding rate in a real-world clinical practice over a 2-year period of 4.6%, which is markedly lower than previous reports with standard clinical practice [4,15,16,[23][24][25][26][27][28][29]. Other studies suggest a re-bleeding rate of 17.2% during the first 12 months following sentinel bleed among patients undergoing band ligation in conjunction with b-blockers for secondary prevention [30], although Includes one patient who suffered a fatal re-bleeding event.…”
Section: Discussioncontrasting
confidence: 72%
“…Our study demonstrated an overall re-bleeding rate in a real-world clinical practice over a 2-year period of 4.6%, which is markedly lower than previous reports with standard clinical practice [4,15,16,[23][24][25][26][27][28][29]. Other studies suggest a re-bleeding rate of 17.2% during the first 12 months following sentinel bleed among patients undergoing band ligation in conjunction with b-blockers for secondary prevention [30], although Includes one patient who suffered a fatal re-bleeding event.…”
Section: Discussioncontrasting
confidence: 72%
“…If the initial bleeding episode is controlled with sclerotherapy, follow-up endoscopic banding can still be performed. The combination of endoscopic banding and sclerotherapy is not more effective than banding alone [15]. Contraindications Inability to visualize the esophagus.…”
Section: Endoscopic Ligation (Banding)mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, the time from treatment to the recurrence of esophageal varices varies markedly between patients, even when the same procedure is performed. Factors affecting the time to recurrence in individuals remain unknown, although this variation may be due partly to differences in the venous structure connected with esophageal varices, and the associated hemodynamics.…”
Section: Introductionmentioning
confidence: 97%